Stress and coping during the COVID-19 pandemic among martial arts athletes - a cross-cultural study - Makarowski, R.; Piotrowski, A.; Predoiu, R.; Görner, K.; Predoiu, A.; Mitrache, G.; Malinauskas, R.; Bochaver, K.; Dovzhik, L.; Cherepov, E.; Vazne, Z.; Vicente-Salar, N.; et al. (Archives of Budo, 2020)
Background and Study Aims: Success in sports among athletes on a similar level of skill can depend on individual differences in experienced stress and coping strategies. The COVID-19 pandemic has affected many areas of life, including sports. The aim of the current study was to verify two hypotheses: (H1) emotional tension, external stress, and intrapsychic stress among martial arts athletes will be significantly higher during the height of the pandemic than in the pre-pandemic period; (H2) martial arts athletes will less frequently use problem-focused strategies of coping with stress, such as active coping and planning, during the height of the pandemic.